The North Korean famine and its demographic impact - Goodkind, D. M.; West, L.
tbls., map.
pp.219-238
Keywords: Hambre; Republica de Corea; Mortalidad; Malnutrición; Mortalidad Infantil; Esperanza de Vida; China